Kegiatan Deteksi Dini Perubahan Komposisi Tubuh Pada Populasi Dewasa Di Sma Santo Yoseph, Cakung - Andria Priyana; Alexannder Halim Santoso; Anthon Eka Prayoga Khoto; Nikita Tan; Dianova Soeltanong; Eric Hartono (PPNI UNIMMAN, 2024)
Increased body fat, especially visceral adipose tissue, is associated with metabolic syndrome and other serious health conditions. Early detection of body composition is essential to identify individuals at risk for metabolic and musculoskeletal disorders, such as obesity, cardiovascular disease, diabetes, and sarcopenia. Body composition can be examined using Karada Omron. The purpose of this community service activity is to determine the body composition of productive-age adults. This activity was carried out at Santo Yoseph High School, East Jakarta, involving 69 participants. This activity was designed using the Plan-Do-Check-Action (PDCA) method. The results showed that 11 men (15.94%) and 47 women (68.12%) had above-normal total body fat levels. As for the whole body skeletal muscle mass, 17 men (24.64%) and 33 women (47.83%) had below-normal muscle mass. Education about healthy eating patterns and regular physical activity is part of an effort to increase public awareness of the importance of maintaining a balanced body composition to improve overall quality of life